INFLUENCE OF DIFFERENT METHODS OF COTTON PICKING ON THE QUALITY OF COTTON - Jumaniyazov, K.; Egamberdiev, F.O.; Abbazov, I.Z.; Gadoyev, N.E. (International Journal of Psychosocial Rehabilitation, 2020)
This article provides information on moisture and impurities in cotton which picked by m hand and different cotton-picking machines, as well as the number of knots in the hand and machine-made cotton fiber, in addition to the length of the staple of the fiber. An analysis of the results of manual and machine research on cotton is represented. The moisture content, the contamination, the number of knots and the length of the staple depend on a number of factors and the results obtained by the methods of their determination are illustrated.The quality of cotton is determined not only by types of machines, but also by the climatic conditions during the harvest, cotton opening, field preparation and other factors, and the contamination by the State Standard UzDst 592 -2008 on the methods of determining the cotton contamination. The results of a practical study ofcomparing moisture and contamination of cotton harvested by hand and by cotton picking machine ''Case-2020'' in Genefon breeder type 1 in the Dustlik district of Jizzakh region of Uzbekistan and contrasting type cotton harvested by JohnDeere by SPD90 and humidity and humidity indicators of hand-picked cotton УСХ or ВХС-М-1, ЛКМ, and number of blanks and length of staples in cotton fiber МЧЖ Jizzakh textile The analysis of the results of the tests performed on the laboratory equipment on the USTER AFIS PRO 2 equipment installed in the laboratory of the divice is presented in table and graphical form. Based on the results of the research, it is stated that it is necessary to develop recommendations on technological processes of cotton processing and spinning based on the analysis of moisture content, contamination, number of sticks and staple lengths of cotton.